Aspectos fisiológicos, celulares e moleculares da dessecação e armazenamento de sementes de Araucaria angustifolia (Bertol.) Kuntze - Gasparin, Ezequiel (2016)
Seeds of Araucaria angustifolia are classified as recalcitrant, so they have limited longevity, making difficult the storage and, consequently, available viable seeds for long time. The species is critically endangered and due the economic importance of the timber and the seeds (pinhão) for food, are necessary studies for ex situ conservation of this species. Therefore, this search had the followed aims: a) evaluated the effect of drying rates on the viability of seeds from two provenances (Minas Gerais e Rio Grande do Sul); b) selecteded reference genes for normalization RT-qPCR data and analyzed the expression levels of genes related to desiccation tolerance of seeds subjected to dehydration; c) evaluated the storability of the seeds from two provenances under refrigeration condition and, d) evaluated the behavior of induced soil seed bank in different forest environments. According to the result, seeds tolerate a slight drying (near 34% water content), maintaining high viability (85% germination), and there was no significant differences between effects of fast and slow drying for both seed provenances. The loss of viability to low water content was associated with abnormal aspect of cell wall, deformation of organelles and subcellular deformation. The gene expression by RT-qPCR showed that the most stable reference genes for heterogeneous samples (intertissues) were ACT, GAPDH and SAR1. For the most genes analysed, there was a decreasing of expression levels of the genes after dehydration, such as ABI3, LEC1, SMP, APX, MIPS e XERO1. Finally, both seed provenances showed storage potential for approximately 12 months, under refrigeration condition. However, A. angustifolia seeds are able to establish transient soil seed bank, which was associated with forest conservation status. Thus, it is possible conclude that A. angustifolia seeds tolerate a slight drying, which may help increase the seeds storability. During the dehydration, the loss of seeds viability to lower water content was associated to cellular damages and decreasing of transcripts levels of genes related to desiccation tolerance. Finally, it is possible storage the seeds during short time for seedling production, and the conservation of forest cover is primordial for species regeneration by soil seed bank.